The Influence of Medan State University Students Academic Fraud Behavior Through the Pentagon Fraud Dimensions - Anjiani, Dila; Lidia, Lidia; Yenni, Restika (Asosiasi Dosen Akuntansi Indonesia, 2023)
The problem in this case is that we, researchers, are motivated to test the dimensions of the Fraud Pentagon, whether using it has a significant influence on the academic fraud of Medan State University students from various faculties. So that from the existence of various faculties, researchers will be able to analyze the comparison of academic fraud in various faculties using the dimensions of the fraud pentagon. This type of research is quantitative research, using a questionnaire as the research instrument. The population used in this research was from various faculties of Medan State University, the number of samples in this research was 32 students. It is hoped that this research can become research that is able to explore information related to pressure and behavior towards academic cheating. Furthermore, the results of this research are expected to reduce academic cheating behavior